Design of Reactor for The Production of Ethanol from Hydration of Ethene - Muhammad Risdan Putra Setiawan (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
The objective of this research is to formulate the design of a Continuous Stirred Tank Reactor (CSTR) employed in ethanol production. The study incorporates mass balance calculations as a reference to assess the reactor's performance by understanding the influx of raw materials and the resultant product output. Additionally, both the reactor and stirrer designs are manually computed using Microsoft Excel in this study. The calculated design for the reactor indicates a volume of 103.09 ft3, featuring a vessel dimension of 51.06 in, a cylinder height of 3.18 in, and a cylinder thickness of 1.74 in. The top cap measures 8.63 in with a thickness of 1.52 in, while the bottom lid measures 14.75 inches with a thickness of 3,49 inches. Consequently, the overall height of the reactor amounts to 2.28 feet. The reactor is furnished with a single stirrer, boasting a shaft diameter of stirrer 6,93 in, and shaft length of stirrer measuring 1,64 feet. Turbulent stirring flow conditions are maintained, and the standard motor power for the stirrer is 713 HP.